Pengaruh Dukungan Kelompok Terhadap Kualitas Hidup Penderita Diabetes Melitus - Ismail, Muhammad Hamid; Yulian, Vinami (Jurnal Berita Ilmu Keperawatan, 2019)
Diabetes mellitus is a major health problem. Diabetes mellitus can be serious and lead to chronic conditions that endanger if not treated. It gives effect to the quality of life of patients with DM. Interviews showed that Persadia members active in Surakarta branch has a health condition and quality of life is further improved compared with DM patients who are not actively participating or not at all health conditions and quality of life to decrease. This study aimed to analyze the influence of support groups on quality of life in patients with DM Surakarta branch Persadia. This study was a correlational analytical survey. The samples are 74 people with diabetes mellitus who were active in Persadia with the determination of purposive sampling techniques. The date collection used questionnaires. Data analysis was performed using univariate and bivariate analysis. The study showed that (1) average price in DM patients support groups active in Persadia Surakarta branch of 66.19, (2) the average quality of life of people with diabetes who were active in Persadia Surakarta branch of 88.51, and (3) there was a positive relationship between the group support with quality of life in patients with DM in Surakarta branch Persadia (p-value = 0.017), hence, the better the group support, the quality of life of people with DM is increasing.